Administrative law - Wade,William (Oxford., 2014)
ade & Forsyth's 'Administrative Law' is the definitive account of the principles of judicial review and the administrative arrangements of the United Kingdom. Firmly established among the foremost rank of legal textbooks, it stands unparalleled in both scope and detail